CORRIDOR-TYPE BAFFLED MIXING BASIN WITH CROSS POROUS BARRIERS - Epoyan, S. M.; Yarkin, V. A.; Sukhorukov, G. I.; Babenko, S. P. (Science and Transport Progress, 2021)
Purpose. The paper hightlights the increase in operational efficiency of corridor-type baffled mixing basin by installing of cross porous barriers made of gravel (or other materials) and epoxy resin, grade ED-20 (ED-16) with the hardener polyethylenepolyamine (PEPA), approved by Ukrainian Ministry of Health in systems of utility and drinking water supply. Methodology. The first stage of the experiments was performed on the model of the proposed mixer in scale 1:4 in order to determine the local resistance of the porous barrier, which is made of gravel with a size of 10-15 mm (average diameter 12.5 mm) and thickness of 50 mm. The local resistance of the barrier was measured using piezometers installed before and after the porous barrier. The velocity of water motion in the corridor of the mixer was determined depending on the water consumption, incoming on the mixer accordingly to the water meter and by the volumetric method. Findings. In accordance with researches when the water flows at a velocity of 0.1 m/s in the corridor of the mixer, the head losses in the porous barrier is 17 cm (0.17 m), and at a velocity of 0.2 m/s–0.68 m. The resistance coefficient (ξ), which is equal to 333.2 for the investigated barrier, was determined experimentally. It allows determining the head losses in the porous barrier at other velocities of water motion. When the velocity of water motion in the corridors of the mixer is from 0.7 up to 0.5 m/s, head losses increase almost fourfold. The conducted researches allowed to develop a calculation methodology for corridor-type baffled mixing basin with porous polymer-concrete barriers. Originality. Authors developed and investigated the corridor-type baffled mixing basin with porous polymer-concrete barriers. These barriers allow increasing and regulating the intensity and time of reagents mixing with the initial water exactly in the barriers, improving the distribution of the flow through the section of the mixer corridors. Practical value. The location of removable porous barriers in the corridors of the baffled mixing basin makes it possible to increase the efficiency of its operation and improve the quality of the treated water.